Effectiveness of the Non‐Medical Surgical Assistant measured by patient outcome assessment. Issue 1 (30th January 2020) - Hains, Toni; Rowell, David; Strand, Haakan
Abstract: Aims: To investigate effectiveness of the nurse clinician as a Non‐Medical Surgical Assistant compared with the Medical Surgical Assistant. Background: Non‐Medical Surgical Assistants are clinicians who are not medical practitioners. The surgical assistant works directly with the primary surgeon intraoperatively. Design: A pragmatic, retrospective, observational study on patients undergoing Laparoscopic Inguinal Hernia Repair or Primary Unilateral Total Hip Arthroplasty. Each patient received intraoperative care from a consultant surgeon and a Medical Surgical Assistant or Non‐Medical Surgical Assistant. All surgical assistants were registered with the Australian Health Practitioner Regulation Agency. Methods: Data were collected between 01/07/2014 and 30/06/2017. The effect that surgical assistant choice had on patient outcomes was estimated using regression statistical models. Six dependent variables, including length of stay, for clinical outcome assessment were specified. Results/Findings: The groups were equivalent in age, gender, and American Society of Anaesthesiologists scores. There were more emergency procedures in the Medical Surgical Assistant group and more hip surgery in the Non‐Medical Surgical Assistant group. Patient outcome assessment showed no statistically significant differences for surgical assistant types. Conclusion: The nurse clinician in the role of Non‐Medical Surgical Assistant was shown to be effective with equivalent patient outcomes compared with the Medical Surgical Assistant. SUMMARY STATEMENT: What is already known about this topic? There is limited international research and no research conducted in Australia, investigating quality of care of the Non‐Medical Surgical Assistant. Existing research on Non‐Medical Surgical Assistants has been limited to a single specialty, which is often cardiac surgery. International research reports equal patient outcomes for the Non‐Medical Surgical Assistant using the comparator of the Medical Surgical Assistant; however, the Non‐Medical Surgical Assistant does not exclusively have a nursing‐based qualification in these studies. What this paper adds? Our study focuses on the two most common surgical specialties in Australia and the Non‐Medical Surgical Assistant with a nursing qualification of either a Registered Nurse or Nurse Practitioner. The results show that the choice of nursing or medical surgical assistant did not affect patient outcomes. The implications of this paper: In Australia, Registered Nurses and Nurse Practitioners can provide effective care in the role of surgical assistant compared with the Medical Surgical Assistant. While patient outcomes are equal, the Registered Nurse and Nurse Practitioner in Australia are not remunerated by the government similarly to the medical personnel undertaking the role of surgical assistant. This raises issues of inequity in the Australian health‐care system for patients accessing surgical care and making the role of surgical assistant unsustainable to non‐medical health‐care personnel. Findings are relevant to the Medicare Benefits Schedule Review Taskforce and access to the Medical Benefits Schedule for Non‐Medical Surgical Assistants.